KERUSAKAN SEL HATI DAN PENINGKATKAN KOLESTEROL SERUM MENCIT AKIBAT PEMBERIAN MINYAK GORENG BEKAS PAKAI - Ika Rahmawati Sutejo (Jurnal Ilmu Kesehatan Masyarakat, 2012)
The purpose of this study were to prove that the administration of heated palm oil can cause hepatocytes damage and cholesterol serum level incerase in mouse. This research was an experimental research using 38 male Mus musculus, Swiss derived. They were divided into 3 groups; 9 were the first negative control by aquadest administration, 9 were the second negative control by fresh palm oil administration, and 20 were intervention by 27-times heated palm oil administration. The dose of administration was 1 ml/100 gram body weight, every day for 14 days. Parameter used in examining liver microscopically was the percentage of hepatocytes getting degeneration of each vision field by 100-times magnificence. The result of microscopic examination were normal hepatocytes for aquadest administration group, fatty degeneration for fresh palm oil administration group, fatty degeneration and central zone necrosis for 27-times heated palm oil group. The average value of cholesterol serum level in aquadest administration group was 101,44 ± 8,71 mg/dl, in fresh palm oil administration group was 104,66 ± 7,75 mg/dl, and in 27-times heated palm oil group was 130,15 ± 12,26 mg/dl. It could be concluded that administration of 27-times heated palm oil for 14 days can cause degeneration of hepatocytes (p<0,05) and cholesterol serum level increase (p<0,05). Keyword: heated palm oil, fatty degeneration, necrosis hepatocyte, cholesterol